A transparência intraorganizacional como princípio da governança pública: aplicação no contexto das contratações em um tribunal regional do trabalho - Hollanda, Dirceu Victor Monte de (2024)
Public organizations, as organisms that thrive on societal demands to strengthen their institutional mission, need to keep pace with social developments manifested through legal or sub-legal regulations, particularly public policies instituted by various governing bodies. Public governance emerged from the realization that the management model based solely on management structures would no longer be sufficient to meet the new standards of complexity and societal demands. With this new public administration model, still in the process of being incorporated into the organizational culture, new concepts, principles, structures, and the challenge of integrating with the previously existing model emerged. Based on a gap identified in the literature and the low performance of a strategic procurement indicator in TRT21-RN, this study proposed a procurement demand monitoring panel that promotes transparency, as a governance principle applied to the intra-organizational environment. The research was characterized by a qualitative, exploratory, and applied approach, using the Design Science Research (DSR) method and data collection methodologies through documentary research, focus groups, and participant observation, with qualitative analyses being carried out in the various stages of the research. From a generic performance problem in procurement processes, the data collected in the focus group ratified the existence of an intra-organizational transparency problem in TRT21-RN and converged on the development of a monitoring panel, integrating the main information contained in the governance and demand management systems, with a focus on procurement. The panel was evaluated and validated by the Focus Group, which also presented its initial perception of the benefits of improving intra-organizational transparency, as a governance principle, mainly to allow a comprehensive view of the organization's demands and enable its systemic monitoring by all its governance and management structures and at all functional levels: strategic, tactical, and operational.